Intercultural Competence and Language Achievements: A Case Study of the Thai Immersions at the Language Institute and Global Affairs,Chiang Rai Rajabhat University - Prathoomthin, Adisorn (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
The study investigates cultural competencies of learners of Thai as a foreign language, titled “Thai Language Learning Achievement: A Case Study of the Thai immersion Program at the Institute of Languages and Foreign Affairs Chiang Rai Rajabhat University”. The aims of the study are twofold: First, to understand learners’ Thai cultural competency who participated in the Thai Immersion Program. Second, to investigate the relationship between learners’ cultural competency and their Thai language competence after they have completed the immersion. The results show that after completing the project, the students’ cultural competency was moderately higher than before, with a statistically significant mean of 2.84 As for cultural competency, which had a statistically significant positive correlation coefficient at the .01 level. The findings were interpreted as the variables had a high level of correlation. That suggests that when learners have achieved higher cultural competency, they were likely to have achieved higher language competence in the Thai language.